A Remark Concerning Bi-Lipschitz Equivalence of Delone Sets [Une Remarque À Propos de L Équivalence Bilipschitzienne Entre Des Ensembles de Delone] - Navas-Flores, A (Elsevier Masson SAS, 2016)
Linearly repetitive Delone sets are shown to be rectifiable by a bi-Lipschitz homeomorphism of the Euclidean space sending it to the standard lattice. © 2016